Manajemen Risiko Produksi Kopi Arabika (Coffea arabica) pada Curtina Coffee Farm di Desa Gunung Bau, Kecamatan Kintamani, Kabupaten Bangli - Ni Kadek Dela Puspitayanti; Ni Luh Prima Kemala Dewi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Curtina Coffee Farm is a processor of Kintamani Arabica coffee that focuses on post-harvest processing. This study aims to identify risks in the production activities at Curtina Coffee Farm, analyze the level of risk using the Failure Mode and Effect Analysis (FMEA) method, and develop mitigation plans to minimize the impact of those risks. The results show that there are 9 risk agents in the Broadly Acceptable (BA) category, 3 risk agents in the As Low As Reasonably Practicable (ALARP) category, and 2 risk agents in the Intolerable (INT) category. The risk with the highest Risk Priority Number (RPN) is the suboptimal performance of the sorting machine, with an RPN value of 448, while the lowest RPN is for the risk that the coffee product does not meet customer quality standards, with a value of RPN 6. Priority handling is focused on risk agents in the INT and ALARP categories, with a total of eight risk agents for which mitigation plans were developed. The formulated mitigation strategies include: (1) Routine maintenance of the sorting machine, (2) Technical training for machine operators, (3) Optimization of fermentation room design, (4) Ventilation systems adjusted to environmental conditions, (5) Scheduled maintenance of the hulling machine, (6) Provision of spare parts for the hulling machine, (7) Development of stricter fermentation standard operating procedures (SOPs), (8) Regular quality testing, (9) Use of mechanical dryers as an alternative, (10) Development of a greenhouse-based drying system